Contracting for care – the construction of the farrier role in supporting horse owners to prevent laminitis. (17th May 2018) - Lynden, J.; Ogden, J.; Hollands, T.
Summary: Background: Emerging research highlights how, due to demographic changes in horse owner populations in Western societies, complex owner–horse relationships are leading to inappropriate horse care, including overnutrition, which in turn can lead to laminitis. Farriers, due to their regular visits, may be in a position to support owners in dealing with this problem. Objectives: This study explored whether UK farriers have a role in working with horse owners to support horse welfare and prevent laminitis. Study design: Grounded theory analysis, a qualitative methodology. Methods: Semi‐structured interviews were conducted with 12 farriers and 11 horse owners. The interviews were transcribed verbatim and systematically analysed, using an inductive coding approach. Results: The analysis of the farrier and horse owner interview data revealed farriers and horse owners undertake a contracting process leading to either a task‐focussed or holistic care‐focussed approach. Either approach can be satisfactory, but the evidence from this study suggests that when horses are at risk of laminitis, a task‐focussed approach misses important opportunities to prevent it. Main limitations: This analysis, based on a small sample of participants, was not able to identify the frequency of farriers or horse owners orientating towards different approaches in a way that can be generalised to a wider population. However, the power of grounded theory lies in its inductive design to develop new theory, which can be subsequently tested. Conclusions: Farriers are in a perfect position to support horse owners to prevent laminitis through providing feedback, guidance and advice. However, not all farriers adopt this role and it is not necessary in all contexts. The evidence presented in this study has implications for equine veterinarians and welfare officers in educating horse owners about the value of holistic care‐focussed farriery.